A Case of Pseudoaneurysm of the Superficial Temporal Artery Causing a Massive Subcutaneous Hematoma after Craniotomy - Tatano, Masaki; Hayashi, Seiya; Yunoki, Masatoshi; Umakoshi, Michiari; Hirashita, Koji; Yoshino, Kimihiro (Asian Journal of Neurosurgery, 2022)
We present a case of a ruptured pseudoaneurysm of the superficial temporal artery (STA) after surgery for intracranial hemorrhage. To our knowledge, only three similar cases have been reported. A 47-year-old man underwent left frontal craniotomy for a left frontal subcortical hematoma. The left STA was not identified during the surgery, and no STA bleeding was observed. The postoperative course was uneventful for 20 days, until the patient experienced a left-side headache and noticed a subcutaneous mass. The mass increase in size within 1 hour and arterial hemorrhage was observed through a tear in the wound. Findings on subsequent contrast computed tomography were consistent with a ruptured pseudoaneurysm arising from the left STA. Emergency evacuation of the hematoma and STA ligation were performed. Pathological findings were consistent with a pseudoaneurysm. STA pseudoaneurysms occasionally grow rapidly and can cause massive hematoma. Surgeons should carefully monitor for evidence of a pseudoaneurysm after craniotomy, even in the absence of intraoperative bleeding from the STA.
Keywords: craniotomy; hematoma; pseudoaneurysm; superficial temporal artery